Roitt's Essential Immunology - Delves, Peter J Martin, Seamus J (Blackwell Publishing, 2006)
'Roitt's Essential Immunology' outdistances other textbooks in the area by its scope, its organisation, its clarity and its ability to convey a carefully balanced and up-to-date view of immunology.